(untitled) (American Journal of Education and Technology, 2023)
The global crisis brought on by the Covid-19 outbreak has affected students’ approaches to education. The teaching and learning processes of teachers and students have also changed due to the crisis. Following the Exploratory Mixed Method design, an interview (qualitative) was employed first followed by a survey (quantitative). A total of fifteen (15) participants participated in the interview phase (qualitative), and four hundred twelve (412) respondents participated in the survey phase(quantitative). Content analysis is used in the analysis of qualitative data and the Kaiser-Meyer-Olkin test and Bartlett’s Test of Sphericity analyses were used to determine the factor loading of the items. The result showed four (4) factors in the formative assessment tools in online-blended learning. These factors include feedback mechanism, satisfaction, internet and technology availability, and overall challenges. Based on the result of the study, a general recommendation is for future researchers to conduct a confirmatory factor analysis for further exploration and confirmation of the said factors of student satisfaction towards formative assessment tools in the online-blended modality of learning.